High-ionic-conductivity polymer solid-state battery, preparation method thereof and power utilization device

By treating the precursor solution of polymer and lithium salt under an electronic irradiation device, a polymer solid-state battery with high ionic conductivity is prepared, which solves the problem of low battery conductivity in the prior art and improves the charge and discharge capacity.

CN119400970APending Publication Date: 2025-02-07STATE POWER INVESTMENT CORPORATION RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411542495.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing polymer solid-state batteries have low ionic conductivity, which affects their charging and discharging capabilities.

Method used

Polymer solid state batteries with high ionic conductivity were prepared by dissolving the polymer and lithium salt in an organic solvent to form a precursor solution and processing under irradiation by an electronic irradiation device.

Benefits of technology

The ionic conductivity of polymer solid-state batteries is improved, its charging and discharging capabilities are enhanced, and the problem of insufficient battery performance in the prior art is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400970A_ABST
    Figure CN119400970A_ABST
Patent Text Reader

Abstract

The invention discloses a high-ionic-conductivity polymer solid-state battery, a preparation method thereof and an electric device. According to the method, the polymer solid-state battery is directly irradiated, so that the ionic conductivity of the polymer solid-state battery is improved, key problems in industrial application of the polymer solid-state battery are improved, in addition, electron irradiation has no obvious irradiation effect on other components of the polymer solid-state battery, the process is simple, and application is convenient; the irradiated polymer solid-state battery prepared by the method is stable and reliable, a solution is expected to be provided for industrial application of the solid-state battery, and mass production and application of all-solid-state batteries in the fields of new energy vehicles, unmanned aerial vehicles, mobile electronic equipment, energy storage and the like are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a high-ion conductivity polymer solid-state battery, a preparation method thereof, and an electrical device thereof. Background Art

[0002] At present, compared with liquid electrolyte lithium-ion batteries, polymer solid-state batteries are safer, have better mechanical properties, and are more processable. At the same time, high-energy-density electrode materials such as metallic lithium can be used to further increase the energy density of the battery. Therefore, polymer solid-state batteries have broad application prospects in various energy storage fields.

[0003] The polymer electrolyte is the core component of the polymer solid-state battery. The polymer electrolyte includes a polymer matrix and a lithium salt. Since ion transport in the polymer electrolyte mainly occurs in the amorphous region, and the unmodified polymer electrolyte has a relatively high crystallinity, the ion conductivity is low, which affects the charge and discharge capacity of the polymer solid-state battery. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] To this end, embodiments of the present invention provide a high ionic conductivity polymer solid-state battery, a preparation method thereof, and an electrical device.

[0006] In a first aspect, the present invention provides a method for preparing a high ionic conductivity polymer solid-state battery, comprising the following steps:

[0007] (a) dissolving a polymer and a lithium salt in a mass ratio of 1:6 to 9:4 in an organic solvent to form a precursor solution, and casting the precursor solution into a film to obtain a polymer solid electrolyte;

[0008] (b) assembling the positive electrode plate, the polymer solid electrolyte and the negative electrode to obtain a polymer solid state battery;

[0009] (c) turning on the electron irradiation equipment to perform electron irradiation on the polymer solid-state battery to obtain an irradiated polymer solid-state battery.

[0010] Among them, electron irradiation equipment is a device that uses high-energy electron beams to irradiate materials to improve material properties. Electron irradiation equipment includes medium-energy electron accelerators (denami type, insulation core transformer type, high-pressure high-voltage transformer type, resonant transformer type, etc.) and high-energy electron accelerators (linear type, etc.).

[0011] Furthermore, the precursor solution also includes an inorganic filler, and the inorganic filler includes an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte, an oxyhalide solid electrolyte, and a composite solid electrolyte thereof.

[0012] Among them, oxide solid electrolytes include garnet type (LLZO), LiPON type, perovskite type, antiperovskite type, NASICON type, and LISICON type; sulfide solid electrolytes include Li-PS type, Argyrodite type, LGPS type, and Thio-LISICON type; halide solid electrolytes include Li-MX type (M includes In, Y, Zr, Ta, La, and X includes F, Cl, and I); composite electrolytes refer to a mixture of two or more of the above inorganic fillers.

[0013] Further, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium perchlorate, and lithium tetrafluoroborate; and / or the organic solvent includes one or more of diethyl carbonate, tetrahydrofuran, dimethyl carbonate, acetone, isopropanol, N-methyl-2-pyrrolidone, and dimethyl sulfoxide.

[0014] Furthermore, the polymer includes one or more of polyacrylonitrile, polymethyl methacrylate, polyphenylene ether, and polyethylene oxide.

[0015] Furthermore, the positive electrode plate is obtained by dissolving a positive electrode active material, a conductive agent, and a binder in an organic solvent, coating the mixture on an aluminum foil, and drying the mixture, wherein the positive electrode active material includes one of lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide.

[0016] Among them, the conductive agent includes one or more of acetylene black, graphene, Super P, conductive carbon black, carbon fiber, carbon nanotubes, Ketjen black, and conductive graphite; the binder includes one or more of polyvinylidene fluoride, polyvinyl carbonate, polytetrafluoroethylene, polyethylene oxide, polypropylene carbonate, and polyethylene.

[0017] Furthermore, the negative electrode includes lithium metal, lithium alloy, carbon material, or silicon material.

[0018] Furthermore, the thickness of the polymer solid-state battery is less than 2 cm.

[0019] Too large a thickness of the polymer solid electrolyte will result in insufficient electron beam irradiation.

[0020] Furthermore, the irradiation temperature of the electron irradiation equipment is 25-200° C., the electron energy is 120 keV-10 MeV, the electron current is 0.1-1000 mA, and the electron irradiation dose is 0.1-100 kGy.

[0021] In some embodiments, the irradiation temperature is room temperature (25°C), 50°C, 80°C, 100°C, 130°C, 150°C, 180°C, 200°C, or a value within a range consisting of any two values. When the irradiation temperature is 25°C, the electron irradiation is performed at room temperature. Irradiation at a suitable irradiation temperature can improve the irradiation efficiency and economy. Too high an irradiation temperature can cause negative cross-linking of the polymer and increase the process cost by increasing the temperature. Too low an irradiation temperature may reduce the irradiation effect and increase the process cost by decreasing the temperature.

[0022] In some embodiments, the electron energy is 120keV, 200keV, 300keV, 400keV, 500keV, 600keV, 700keV, 800keV, 900keV, 1MeV, 2MeV, 3MeV, 4MeV, 5MeV, 6MeV, 7MeV, 8MeV, 9MeV, 10MeV or a value in a range consisting of any two values. Irradiation under appropriate electron energy conditions can obtain appropriate irradiation effects, improve irradiation efficiency and economy. Too high electron energy may cause negative crosslinking and increase equipment costs. Too low electron energy may cause insufficient penetration depth of the electron beam, which may result in insufficient irradiation or low irradiation efficiency.

[0023] In some embodiments, the electron current intensity is 0.1 mA, 0.5 mA, 1 mA, 5 mA, 10 mA, 30 mA, 50 mA, 60 mA, 80 mA, 100 mA, 200 mA, 400 mA, 500 mA, 700 mA, 900 mA, 1000 mA, or a value in a range consisting of any two values. Irradiation under appropriate electron current intensity conditions can obtain appropriate irradiation effects and improve irradiation efficiency. Too high electron current intensity may produce too strong a thermal effect in the solid electrolyte. Too low electron current intensity may result in too low irradiation efficiency and too long irradiation time.

[0024] In some embodiments, the electron irradiation dose is a value within a range consisting of any two values ​​of 0.1 kGy, 0.5 kGy, 0.9 kGy, 1 kGy, 3 kGy, 5 kGy, 8 kGy, 10 kGy, 20 kGy, 30 kGy, 40 kGy, 50 kGy, 60 kGy, 70 kGy, 80 kGy, 90 kGy, and 100 kGy. Irradiation under appropriate electron irradiation dose conditions can obtain appropriate irradiation effects and improve economic efficiency. Too high an electron irradiation dose may cause negative cross-linking and increase process costs. Too low an electron irradiation dose may result in insufficient irradiation effects.

[0025] In a second aspect, the present invention proposes a high ionic conductivity polymer solid-state battery prepared by the method proposed in the first aspect.

[0026] In a third aspect, the present invention proposes an electrical device comprising a high ion conductivity polymer solid-state battery prepared by the method proposed in the first aspect or a high ion conductivity polymer solid-state battery proposed in the second aspect.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] The direct irradiation of the polymer solid-state battery of the present invention improves its ionic conductivity, thereby improving the key problems faced in the industrial application of the polymer solid-state battery. In addition, electron irradiation has no significant irradiation effect on other components of the polymer solid-state battery (positive and negative electrodes, etc.), and the process is simple and easy to use.

[0029] The irradiated polymer solid-state battery prepared by the method of the present invention is stable and reliable, and is expected to provide a solution for the industrial application of solid-state batteries, and promote the mass production and application of all-solid-state batteries in new energy vehicles, drones, mobile electronic devices, energy storage and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0031] Figure 1 The present invention is a flow chart of the preparation method of the high ionic conductivity polymer solid-state battery. DETAILED DESCRIPTION

[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0033] Please refer to the attached Figure 1 The present invention is specifically described in combination with the following examples and comparative examples. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0034] Example 1

[0035] 1.2 g of polyacrylonitrile (PAN) and 2.0 g of lithium hexafluorophosphate were mixed and dissolved in 18 ml of THF solvent, and the mixture was stirred at 50°C for 15 h, then 0.2 g of inorganic filler TiO2 was added and stirred for 12 h until the mixture was evenly dispersed to obtain a precursor solution; the precursor solution was cast on a polytetrafluoroethylene template and dried at 65°C for 50 h to obtain a polymer electrolyte, which was then cut into Φ16 discs for later use.

[0036] 8g LiFePO4 was mixed with 1g conductive agent SP, 1g PVDF and 40ml NMP were added, and the mixture was stirred for 4h to obtain positive electrode slurry, which was coated on aluminum foil and dried at 65°C for 7h to obtain positive electrode sheets. The positive electrode sheets were cut into Φ12 discs and dried at 60°C in vacuum for 20h.

[0037] In a glove box filled with argon, metal lithium was cut into Φ14 discs. The prepared positive electrode sheet, polymer electrolyte, and negative electrode were assembled into a polymer solid-state battery with a thickness of 10 mm.

[0038] The electron irradiation equipment was turned on, and the irradiated polymer solid-state battery was obtained under the conditions of room temperature, electron energy of 120 keV, electron current of 200 mA, and electron irradiation dose of 20 kGy.

[0039] Example 2

[0040] The difference from Example 1 is that the irradiated polymer solid-state battery is obtained by irradiation at an irradiation temperature of 200° C., an electron energy of 1 MeV, an electron current of 0.1 mA, and an electron irradiation dose of 100 kGy.

[0041] Example 3

[0042] The difference from Example 1 is that the irradiated polymer solid-state battery is obtained by irradiation at an irradiation temperature of 100° C., an electron energy of 10 MeV, an electron current of 1000 mA, and an electron irradiation dose of 0.1 kGy.

[0043] Example 4

[0044] The difference from Example 1 is that the prepared positive electrode plate, polymer electrolyte, and negative electrode are assembled into a polymer solid-state battery with a thickness of 20 mm.

[0045] Example 5

[0046] The difference from Example 1 is that no inorganic filler is added during the preparation of the precursor solution.

[0047] Example 6

[0048] The difference from Example 1 is that the precursor solution is prepared using polymer polymethyl methacrylate. Specifically, 1.2 g of polymethyl methacrylate and 2.0 g of lithium hexafluorophosphate are mixed and dissolved in 18 ml of THF solvent, stirred at 50°C for 15 hours, then 0.2 g of inorganic filler TiO2 is added, and stirred for 12 hours until uniformly dispersed to obtain a precursor solution.

[0049] Example 7

[0050] The difference from Example 1 is that the precursor solution is prepared using polymer polyphenylene ether. Specifically, 1.2 g of polyphenylene ether and 2.0 g of lithium hexafluorophosphate are mixed and dissolved in 18 ml of THF solvent, stirred at 50°C for 15 hours, and then 0.2 g of inorganic filler TiO2 is added and stirred for 12 hours until the precursor solution is evenly dispersed.

[0051] Example 8

[0052] The difference from Example 1 is that the precursor solution is prepared using polymer polyethylene oxide. Specifically, 1.2 g polyethylene oxide and 2.0 g lithium hexafluorophosphate are mixed and dissolved in 18 ml THF solvent, stirred at 50° C. for 15 h, then 0.2 g inorganic filler TiO2 is added, and stirred for 12 h until uniformly dispersed to obtain a precursor solution.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that the prepared positive electrode plate, polymer electrolyte, and negative electrode are assembled into a polymer solid-state battery with a thickness of 30 mm.

[0055] Comparative Example 2

[0056] The difference from Example 1 is that the electron irradiation process is not performed.

[0057] Comparative Example 3

[0058] The difference from Example 2 is that the electron irradiation process is not performed.

[0059] Comparative Example 4

[0060] The difference from Example 3 is that the electron irradiation process is not performed.

[0061] Comparative Example 5

[0062] The difference from Example 5 is that the electron irradiation process is not performed.

[0063] Comparative Example 6

[0064] The difference from Example 6 is that the electron irradiation process is not performed.

[0065] Comparative Example 7

[0066] The difference from Example 7 is that the electron irradiation process is not performed.

[0067] Comparative Example 8

[0068] The difference from Example 8 is that the electron irradiation process is not performed.

[0069] Test Example 1

[0070] The polymer solid-state batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 8 were tested for ionic conductivity. The all-solid-state battery was disassembled to obtain a solid electrolyte membrane. In order to test the conductivity of the electrolyte membrane, stainless steel (Fe) was first used as a blocking electrode to assemble a symmetrical battery of Fe|electrolyte membrane|Fe, and the battery shell was a 2032 battery shell. After assembly, the test battery was placed in a constant temperature and humidity chamber and tested at the set temperature (25°C). The Shanghai Chenhua electrochemical workstation CHI760E was used for AC impedance testing with a frequency range of 0.1Hz to 1MHz, an amplitude of 0.05V, a standing time of 2 seconds, and an open circuit voltage set according to the actual value. The impedance value in the high-frequency region was fitted by the Nyquist diagram, combined with the thickness and area of ​​the electrolyte membrane, and the formula was used. Calculate the conductivity. Where: σ is the ionic conductivity, in Siemens per centimeter (S cm -1 ); d is the thickness of the electrolyte membrane measured after the EIS test, in centimeters (cm); Re is the total resistance of charge transfer recorded by the EIS test, in ohms (Ω); S is the actual contact area between stainless steel (Fe) and the solid polymer electrolyte membrane, that is, the area of ​​the SS spacer layer (1.89 cm 2 ).

[0071] The test results are shown in Table 1 below.

[0072] Table 1:

[0073] Grouping Ionic conductivity (S / cm) Example 1 <![CDATA[5.3×10 -4 ]]> Example 2 <![CDATA[6.0×10 -5 ]]> Example 3 <![CDATA[9.2×10 -5 ]]> Example 4 <![CDATA[5.2×10 -4 ]]> Example 5 <![CDATA[6.1×10 -6 ]]> Example 6 <![CDATA[8.1×10 -5 ]]> Example 7 <![CDATA[9.1×10 -5 ]]> Example 8 <![CDATA[6.1×10 -4 ]]> Comparative Example 1 <![CDATA[4.0×10 -5 ]]> Comparative Example 2 <![CDATA[3.9×10 -5 ]]> Comparative Example 3 <![CDATA[4.2×10 -5 ]]> Comparative Example 4 <![CDATA[4.2×10 -5 ]]> Comparative Example 5 <![CDATA[3.5×10 -7 ]]> Comparative Example 6 <![CDATA[9.0×10 -7 ]]> Comparative Example 7 <![CDATA[1.3×10 -6 ]]> Comparative Example 8 <![CDATA[4.0×10 -5 ]]>

[0074] By comparing Examples 1 to 8 and Comparative Examples 2 to 8, it can be seen that the polymer solid electrolyte obtained by the electron irradiation process has a higher ionic conductivity.

[0075] By comparing Example 1, Example 4 and Comparative Example 1, it can be seen that when the thickness of the polymer solid-state battery is too large, the ionic conductivity of the electrolyte membrane of the irradiated polymer solid-state battery is relatively low.

[0076] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0077] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0078] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a high ionic conductivity polymer solid-state battery, characterized in that: The following steps are involved: (a) dissolving a polymer and a lithium salt in a mass ratio of 1:6 to 9:4 in an organic solvent to form a precursor solution, and casting the precursor solution into a film to obtain a polymer solid electrolyte; (b) assembling the positive electrode plate, the polymer solid electrolyte and the negative electrode to obtain a polymer solid state battery; (c) turning on the electron irradiation equipment to perform electron irradiation on the polymer solid-state battery to obtain an irradiated polymer solid-state battery.

2. The method according to claim 1, characterized in that The precursor solution also includes an inorganic filler, which includes an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte, an oxyhalide solid electrolyte, and a composite solid electrolyte thereof.

3. The method according to claim 1, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium perchlorate, and lithium tetrafluoroborate; and / or the organic solvent includes one or more of diethyl carbonate, tetrahydrofuran, dimethyl carbonate, acetone, isopropanol, N-methyl-2-pyrrolidone, and dimethyl sulfoxide.

4. The method according to claim 1, characterized in that The polymer includes one or more of polyacrylonitrile, polymethyl methacrylate, polyphenylene ether, and polyethylene oxide.

5. The method according to claim 1, characterized in that The positive electrode plate is obtained by dissolving a positive electrode active material, a conductive agent, and a binder in an organic solvent, coating the mixture on an aluminum foil, and drying the mixture. The positive electrode active material includes one of lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide.

6. The method according to claim 1, characterized in that The negative electrode includes lithium metal, lithium alloy, carbon material, and silicon material.

7. The method according to claim 1, characterized in that The thickness of the polymer solid-state battery is less than 2 cm.

8. The method according to claim 1, characterized in that The irradiation temperature of the electron irradiation equipment is 25-200° C., the electron energy is 120 keV-10 MeV, the electron current intensity is 0.1-1000 mA, and the electron irradiation dose is 0.1-100 kGy.

9. A high ionic conductivity polymer solid-state battery, characterized in that: The method is prepared by any one of claims 1 to 8.

10. An electrical device, characterized in that: Comprising the high ionic conductivity polymer solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Preparation method for polymer solid-state battery with wide temperature range

    CN109390632A

  • Solid polymer electrolyte and preparation method and application thereof

    CN116284888A